KAJIAN PEMBUATAN MASKER WAJAH ORGANIK DARI CAMPURAN AMPAS KOPI, AMPAS TEH HIJAU, KUNYIT DAN TEPUNG BERAS: The Face Mask Formulation Is Made from A Mixture of Coffee Residues, Green Tea, Turmeric, And Rice Flour - Ferdi Yudanto; Dea Agustina; Mulan Antikasari Romadloni; Muhammad Fuad Fauzul Mu'tamar (Universitas Darussalam Gontor, 2022)
Currently, there is an increase in the culture of drinking coffee in Indonesia, especially among teenagers. The rise in coffee consumption also increases the number of coffee residues. Coffee grounds are usually thrown away, even though there are still nutrients beneficial for skin health. This study aims to examine the manufacture of organic face masks from a mixture of coffee grounds, green tea, turmeric, and rice flour which contain compounds beneficial for beauty. Face masks are beauty products that are used to treat facial health. In this study, masks were made with only one formulation, namely 50% coffee grounds, 20% rice flour, 20% turmeric, and 10% green tea powder. The test parameters in this study were pH, drying time, and organoleptic tests for aroma, color, texture, and overall preference. The results showed a pH value of 7.1, under the SNI range. The time for the coffee grounds mixture to dry is ±11 minutes. The average value of the overall preference test is 6.5, which means the panelists quite like it. This study proves that the face mask from the mixture of coffee residues follows the characteristics of the face mask innovator products on the market and is under SNI.